Functional requirement of the Arabidopsis importin‐α nuclear transport receptor family in autoimmunity mediated by the NLR protein SNC1. (25th December 2020) - Lüdke, Daniel; Roth, Charlotte; Kamrad, Sieglinde A.; Messerschmidt, Jana; Hartken, Denise; Appel, Jonas; Hörnich, Bojan F.; Yan, Qiqi; Kusch, Stefan; Klenke, Melanie; Gunkel, Annette; Wirthmueller, Lennart; et al.
SUMMARY: IMPORTIN‐α3/MOS6 (MODIFIER OF SNC1, 6) is one of nine importin‐α isoforms in Arabidopsis that recruit nuclear localization signal‐containing cargo proteins to the nuclear import machinery. IMP‐α3 / MOS6 is required genetically for full autoimmunity of the nucleotide‐binding leucine‐rich repeat immune receptor mutant snc1 ( suppressor of npr1‐1, constitutive 1 ) and MOS6 also contributes to basal disease resistance. Here, we investigated the contribution of the other importin‐ α genes to both types of immune responses, and we analyzed potential interactions of all importin‐α isoforms with SNC1. By using reverse‐genetic analyses in Arabidopsis and protein−protein interaction assays in Nicotiana benthamiana, we provide evidence that among the nine α‐importins in Arabidopsis, IMP‐α3/MOS6 is the main nuclear transport receptor of SNC1, and that IMP‐α3 / MOS6 is required selectively for autoimmunity of snc1 and basal resistance to mildly virulent Pseudomonas syringae in Arabidopsis . Significance Statement: Specific requirement for the Arabidopsis α‐importin MOS6 in snc1 ‐mediated autoimmunity is explained by selective formation of MOS6‐SNC1 nuclear import complexes.